2020
DOI: 10.1186/s12889-020-8360-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of depression and its associated factors among patients with diabetes mellitus at Tirunesh-Beijing general hospital, Addis Ababa, Ethiopia

Abstract: Background: Depression is one of the common and overwhelming mental disorder in diabetic patients. A little is known about the prevalence and associated factors of depression among diabetic patients at general hospitals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(52 citation statements)
references
References 24 publications
5
45
2
Order By: Relevance
“…Our study showed that glycaemic control was not a significant risk for developing depression among patients with T2DM. This is a similar outcome to the non-significant association of depression and glycaemic control using fasting blood sugar as reference in patients with T2DM found in Ethiopia [ 31 , 45 ] and subjects with DM in Nigeria [ 43 ]. In contrast, a significant difference between depression and poor glycaemic control (HbA1c > 7%) among patients with DM was documented in Sudan [ 23 ], Guinea [ 39 ], Ghana [ 19 ] and South Africa [ 40 ].…”
Section: Discussionsupporting
confidence: 82%
“…Our study showed that glycaemic control was not a significant risk for developing depression among patients with T2DM. This is a similar outcome to the non-significant association of depression and glycaemic control using fasting blood sugar as reference in patients with T2DM found in Ethiopia [ 31 , 45 ] and subjects with DM in Nigeria [ 43 ]. In contrast, a significant difference between depression and poor glycaemic control (HbA1c > 7%) among patients with DM was documented in Sudan [ 23 ], Guinea [ 39 ], Ghana [ 19 ] and South Africa [ 40 ].…”
Section: Discussionsupporting
confidence: 82%
“…Such a problem negatively impacts communities' health status, resulting in a destructive consequence on mental health status. This doubles the problem for patients and people around them, resulting in irrevocable consequences on countries' health systems (Engidaw et al, 2020). However, diabetes mellitus (DM) is a metabolic disorder characterized by chronic hyperglycemia that causes carbohydrate, protein, and fat metabolism disorders (WHO, 2016;Lebovitz, 2000;Anderson et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…4 Despite this, a systematic review on prevalence and related acute and chronic complications shows insufficient priority given to diabetes and interventions to prevent acute and long-term complications are lacking in Ethiopia at a national level with the major focus of the country on combating infectious disease. 5,6 Depression is a state of depressed mood, low energy and poor concentration, feelings of guilt or low self-worth, loss of interest or pleasure, disturbed sleep or appetite, and aversion to activity affecting a person's behavior and feelings, thoughts, and sense of wellbeing. 7,8 It is the second leading cause of burden of disease, with around 340 million people of all ages suffering from depression globally.…”
Section: Introductionmentioning
confidence: 99%
“…20 In general, a number of studies showed that the presence of untreated depression in patients with DM is associated with the burden of complications, financial stress, poor overall health status, poor glycemic control, decreased the quality of life and increases mortality. 6 Given one of the top five countries with the highest number of people affected by DM in sub-Saharan Africa (SSA) and depression, contributing the highest share of burden compared to other forms of mental disorders, 9 there is limited information regarding the status of depression specifically among T2DM patients in Ethiopia. Hence, the purpose of this study was to determine the magnitude of untreated depression and associated factors among people living with T2DM at an outpatient diabetic clinic in Halaba Kulito General Hospital, Southern Ethiopia.…”
Section: Introductionmentioning
confidence: 99%